Turkey and the Eurasian integration: Ideology or pragmatism? - ERŞEN, EMRE (My University, 2022)
© 2022, RUDN UNiversity. All rights reserved.While Eurasianism as a political ideology has made a remarkable comeback to the Russian political scene following the dissolution of the Soviet Union in 1991, it has also attracted considerable interest among Turkish political and intellectual circles since the early 1990s. Yet, Eurasianism in the Turkish context has acquired different ideological meanings in time. In this regard, it is possible to highlight two main strands of Eurasianism in Turkey: One focusing on the prospects for advanced integration between Turkey and the Turkic republics of the Caucasus and Central Asia, and other concentrating on Turkey\"s strategic cooperation with Russia and China as an alternative to its long-standing ties with the West. While the first approach mainly appeals to nationalistconservative groups in Turkey, the second is supported by the so-called national-patriotic groups. The article aims to discuss Turkey\"s role in two Eurasia-based international organizations — the Organization of Turkic States and the Shanghai Cooperation Organization — as they respectively correspond to the two versions of Eurasianism in Turkey. By analyzing the Turkish governments\" policies towards these two organizations, it would also be possible to reveal the influence of Eurasianism as an ideology on Ankara\"s official approach to the idea of Eurasian integration, in which pragmatic political and economic concerns play an equally important role.
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Sosyoloji; Bilim, Teknoloji ve Toplum; Social Sciences and Humanities; History; Sociology; Science, Technology and Society; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; Sosyal Bilimler Genel; TARİH; PLANLAMA VE GELİŞİM; SİYASET BİLİMİ; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; SOCIAL SCIENCES, GENERAL; HISTORY; PLANNING & DEVELOPMENT; POLITICAL SCIENCE; Gelişim; Sosyal Bilimler ve Beşeri Bilimler; Siyasi bilimler ve Uluslararası İlişkiler; Development; Social Sciences & Humanities; Political Science and International Relations; Eurasian integration; Eurasianism; Organization of Turkic States; Shanghai Cooperation Organization; Turkey